Comparative phylogeography of eight herbs and lianas (Marantaceae) in central African rainforests - Ley, Alexandra C.; Dauby, Gilles; Köhler, Julia; Wypior, Catherina; Röser, Martin; Hardy, Olivier J. (Frontiers in Genetics, 2014)
Vegetation history in tropical Africa is still to date hardly known and the drivers of population differentiation and speciation processes are little documented. It has often been postulated that population fragmentations following climate changes have played a key role in shaping the geographic distribution patterns of genetic diversity and in driving speciation. Here we analyzed phylogeographic patterns (chloroplast-DNA sequences) within and between eight (sister) species of widespread rainforest herbs and lianas from four genera of Marantaceae (Halopegia, Haumania, Marantochloa, Megaphrynium), searching for concordant patterns across species and concordance with the Pleistocene refuge hypothesis. Using 1146 plastid DNA sequences sampled across African tropical lowland rainforest, particularly in the Lower Guinean (LG) phytogeographic region, we analyzed intra- and interspecific patterns of genetic diversity, endemism and distinctiveness. Intraspecific patterns of haplotype diversity were concordant among most species as well as with the species-level diversity pattern of Marantaceae. Highest values were found in the hilly areas of Cameroon and Gabon. However, the spatial distribution of endemic haplotypes, an indicator for refuge areas in general, was not congruent across species. Each proposed refuge exhibited high values of endemism for one or a few species indicating their potential role as area of retraction for the respective species only. Thus evolutionary histories seem to be diverse across species. In fact, areas of high diversity might have been both refuge and/or crossing zone of recolonization routes i.e. secondary contact zone. We hypothesize that retraction of species into one or the other refuge happened by chance depending on the species´ distribution range at the time of climate deterioration. The idiosyncratic patterns found in Marantaceae species are similar to those found among tropical tree species, especially in southern LG.